Kebijakan Moderasi Pidana Mati dalam RUU KUHP Perspektif Nilai-Nilai Pancasila - Sugeng Riyadi; Beny Timor Prasetyo (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2021)
Draft Law on the Criminal Code (RUU KUHP) still gives place to the death penalty as a type of crime. This policy is in the line of the establishment of the Constitutional Court which considers the death penalty to be constitutional. Even though there has been a decision on the constitutionality of the death penalty, the polemic about its existence still continues. So that we do not sway with various opinions, it is necessary that the death penalty policy is viewed from the perspective of Pancasila, because Pancasila is a legal ideal and at the same time as a Fundamental Norm of the Unitary State of the Republic of Indonesia. This study aims to answer whether the death penalty moderation policy in the Criminal Code Bill is justified from the perspective of Pancasila or not. This research is a doctrinal legal research with a statutory approach, a conceptual approach and a philosophical approach. The results showed that the death penalty policy in the Draft Criminal Code does not conflict with Pancasila.